Metal frame overdenture retained with metal medium coping and magnet - Santoso, Tania; Endang Wahyuningtyas; Murti Indrastuti; Pramudya Aditama (Indonesian Journal of Prosthodontic, 2025)
ABSTRACT Overdenture is a removable denture that replaces partial or complete tooth loss and rests on remaining natural teeth or implants. The overdenture concept of avoiding bone resorption can be used as a continuation of root canal treatment so that the alveolar bone remains well preserved. This case report describes prosthodontic rehabilitation with coping and magnet overdentures to increase retention, stability, and reduce bone resorption that will occur due to tooth extraction. A 65-year-old female patient wanted to have new dentures because the old dentures were loose and unaesthetic. Overdentures with metal medium coping and a magnet were made to increase retention for the new upper denture. A metal medium coping with a length of 3–4 mm on the second upper molar can increase retention by the friction force between the coping and the denture. A fabricated magnet, 3.6 mm in diameter with an attractive force of 700±50 gf, was mounted on the denture base, and the keeper was cemented to the second upper premolar as a supporting tooth. The metal frame overdentures provided excellent retention, stability, functionally, and aesthetics. Metal frame overdentures can be treatment of choice to increase the retention and stabilization of dentures. Keywords: Metal frame overdenture, Medium coping, Magnet